2017
DOI: 10.1002/hc.21396
|View full text |Cite
|
Sign up to set email alerts
|

A DFT study of O2 and Cl2 adsorption onto Al12N12 fullerene‐like nanocluster

Abstract: In this study, the adsorption and dissociation of chlorine and oxygen molecules on the surface of Al12N12 nanocluster have been investigated by density functional theory (DFT). Traditional B3LYP and dispersion‐corrected (ωB97XD) functionals have been used to optimize the studied structures. One relaxed structure for adsorbed Cl2 and two for adsorbed O2 (denoted as P1 and P2 configurations) have been found. Both functionals showed strong chemisorption of O2 compared to Cl2 on nanocluster. The dispersion‐correct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…As an example, we studied, by theory, the modification of graphene by decoration of platinum atom in its structure. [12,13] We used this modified graphene as adsorbent for NO [12] and N 2 O. [13] Fullerene-like semiconductors have engrossed enormous attentions nowadays because of their proper physical and chemical properties.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As an example, we studied, by theory, the modification of graphene by decoration of platinum atom in its structure. [12,13] We used this modified graphene as adsorbent for NO [12] and N 2 O. [13] Fullerene-like semiconductors have engrossed enormous attentions nowadays because of their proper physical and chemical properties.…”
mentioning
confidence: 99%
“…[12,13] We used this modified graphene as adsorbent for NO [12] and N 2 O. [13] Fullerene-like semiconductors have engrossed enormous attentions nowadays because of their proper physical and chemical properties. [20][21][22][23] Principally, nanostructured III-V semiconductors have been used in fast microelectronic devices and light-emitting diodes.…”
mentioning
confidence: 99%
“…Based on DFT calculations, the values of binding energy for the SF on graphane, graphene, and CaO surfaces were found to be 6.4, 4.8, and 18.8 kcal/mol, respectively 18 . Moreover, the adsorption of some molecules such as phosgene, H 2 , H 2 O and H 2 S, O 3 and SO 2 , dimethyl ether, Cl 2 and O 2 , and so forth 28–32 and the adsorption of common biomolecules including vitamin C and 4‐aminopyridine have also been investigated on the surface of B 12 N 12 , B 12 P 12 , Ca 12 O 12 , Al 12 P 12 , and Al 12 N 12 nanoclusters in earlier reports 33,34 . The objective of this work is to describe surface interactions at high accuracy using theory in order to understand the details of the removal of toxic agents such as SF and SC by the Al 12 N 12 and Al 12 P 12 nanoclusters.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Choi et al theoretically studied CO2 capture by boron-rich BNNT [7], Rahmanifar et al showed that boron doping improves the reactivity of single-walled CNTs [8]. Very recent studies of Shokuhi Rad et al have shown that B doping also enhances the ozone adsorption by graphene [9]. The comprehensive work of Wang and Guo has shown that boron-rich doping of BNNTs significantly enhances adsorption of the noble gases [10].…”
Section: Introductionmentioning
confidence: 99%